The Rise of Byzantion: Between the Orient and the Occident - Lozanova-Stantcheva, Vanya (Дриновський збірник, 2020)
The focus of this paper is on some aspects of the early pre-emporial (Thracian) stages of Byzantion. The mythological evidence on the city’s emergence, combined with the numismatic material, is systematised and analysed with a view to localising the initial Thracian settlements in the region of the Golden Horn: their synoecism gradually gave birth to the phenomenal city that attracted the attention of the ancient authors only after the emergence of the Greek apoikia. Its unique geographic and strategic location between the Orient and the Occident was not always desired and appreciated, especially during the first half of the first millennium BC, at the time of a dynamic ethnic and cultural situation in Southeastern Europe, and strong military and political activity of the Thracian tribes. The legendary figures, dramatised in the mythological events of the emergence and founding of the city, are extremely deeply rooted in the toponymy of its region, which betrays their profound pre-emporial antiquity. On the other hand, the combined evidence of the ancient authors outlines the roots and the genesis of the local solar cult that is at the centre of the religious traditions of Byzantion. A new interpretation is proposed for some images on the city’s coins in the context of the local mythological traditions.